URGENSI HUKUM PERIKATAN TERHADAP PASIEN YANG TIDAK SADARKAN DIRI DALAM PERTOLONGAN DI IGD - Sidi, Redyanto; Juliandri, Ronnie (BULETIN KONSTITUSI, 2022)
AbstractHealth services are divided into public health services and individual services. In this connection the doctor is the person who is needed and trusted to be able to provide assistance in trying to treat a patient who is in need of a medical treatment. The relationship between doctors and patients at the time of individual health services begins when a patient first comes to the practice room with a complaint about his health. A doctor will conduct a series of initial examinations in the form of an interview called anamnesa, followed by a physical examination that leads to a patient diagnosis. The formulation of the problem in this study is how is the legal protection for patients based on the Civil Code, how is the hospital's responsibility for patients who are unconscious during first aid in the ER, how are the guidelines for emergency services based on health law. The method used in this research is a normative juridical research method. The results of the study indicate that the hospital's legal responsibility in the practice of health services and medical practice in hospitals should be applied not to deviate from Law Number 44 of 2009 concerning Hospitals, Law Number 36 of 2009 concerning Health, Law Number 36 of 2009 concerning Hospitals. 2014 concerning Health Workers, Law Number 29 of 2004 concerning Medical Practice and Law Number 38 of 2014 concerning Nursing. This is because the legal responsibility of hospitals in resolving medical service disputes in Indonesia requires benefits according to the principle of.